The Role Of Community Service In Post-Covid-19 Economic Recovery Through Msme Program - Santoso, Bambang; Fatchurohin, Nur Rosyid; Asnada, Rosada Tri; Ali Nurdin, Muhammad (GEMA EKONOMI, 2022)
UMKM (Micro, Small and Medium Enterprises) is a micro economic sector that is in direct contact with the economic practices of the community, especially people in the middle to lower economic scale. The existence of the Covid-19 pandemic has made people aware that MSMEs are one solution to meet their daily needs because they do not involve the industrial sector or cooperation with foreign countries. This study aims to analyze Indonesia's economic recovery strategy after the COVID-19 pandemic in the MSME sector through the MSME program. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that the strategy in restoring the Indonesian economy, especially in the MSME sector, is in the form of assistance programs, MSME empowerment programs and reducing production costs. Through the aid program, the government has budgeted Rp 123 trillion to help these low-income businesses survive. In addition to providing capital assistance, the government has budgeted an interest subsidy of up to Rp 35 trillion. Meanwhile, in the MSME empowerment program, the government provides counseling about digitalization of marketing. Another strategy is to reduce the production of goods or services and reduce the number of employees.